2001
DOI: 10.1038/labinvest.3780248
|View full text |Cite
|
Sign up to set email alerts
|

CXCR3 Chemokine Receptor Distribution in Normal and Inflamed Tissues: Expression on Activated Lymphocytes, Endothelial Cells, and Dendritic Cells

Abstract: SUMMARY:Using new human CXCR3 chemokine receptor-specific monoclonal antibodies, we studied human CXCR3 tissue distribution in lymphoid and nonlymphoid organs, as well as in inflammatory conditions, including rheumatoid arthritis, Hashimoto's thyroiditis, and dermal vasculitis. CXCR3 was expressed by certain dendritic cell subsets, specifically myeloidderived CD11c positive cells, not only in those present in normal lymphoid organs, but also in germinal centers generated in inflammatory conditions. CXCR3 expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
99
1
4

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(108 citation statements)
references
References 41 publications
4
99
1
4
Order By: Relevance
“…CCL21 could directly or indirectly induce the expression of the requisite adhesion molecules (such as MAdCAM-1 and PNAd), which could then facilitate initial infiltration of lymphocytes. At least one of the CCL21 receptors, CXCR3, has been identified in vascular structures (45,46) and could in theory mediate this effect. Alternatively, CCL21 could act on a bystander cell to induce the production of factors that would affect the expression of adhesion molecules in the endothelium.…”
Section: Discussionmentioning
confidence: 99%
“…CCL21 could directly or indirectly induce the expression of the requisite adhesion molecules (such as MAdCAM-1 and PNAd), which could then facilitate initial infiltration of lymphocytes. At least one of the CCL21 receptors, CXCR3, has been identified in vascular structures (45,46) and could in theory mediate this effect. Alternatively, CCL21 could act on a bystander cell to induce the production of factors that would affect the expression of adhesion molecules in the endothelium.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo analysis of these polarized Th cells has revealed differential sets of molecular expression, including specific chemokine/chemokine receptors. Typically, the chemokine receptor CXCR3 is expressed exclusively on Th1 lymphocytes, which migrate to the inflammatory sites in response to CXCR3 ligands and interferon-inducible protein (IP)-10 [13,14] . Likewise, CCR4 is preferentially expressed on Th2 cells [15] .…”
Section: Introductionmentioning
confidence: 99%
“…There is a good body of evidence that chemokines and their ligands are involved in tubular injury during inflammation. For example, the CXCR3 ligand IFN-␥-inducible protein-10 (IP-10), 3 is up-regulated in animal models of interstitial nephritis (16). In adriamycin nephropathy, high levels of glomerular IP-10 mRNA expression and glomerular and tubulointerstitial IP-10 protein expression are associated with proteinuria and interstitial cellular infiltrates.…”
mentioning
confidence: 99%
“…These chemokine families are defined by the presence of either a C, a CC, a CXC, or a CЈC residue at the N terminus of the protein (1). Until recently, chemokine receptors were regarded mainly as effectors of immunological mechanisms like inflammation, autoimmune disease, and allograft rejection (2)(3)(4). Not until very recently has it been shown that chemokine receptors can be expressed on a variety of nonhemopoietic cells like Purkinje cells (5) and endothelial cells (6,(7)(8)(9).…”
mentioning
confidence: 99%